Chavos banda: transgresión o conformismo - Laura Collin (Estudios sobre las Culturas Contemporáneas)
A light text where authoress Collin talks about profile and behavior of gangs, its daily way of living and their interaction inside of the dinamics of urban life. Through a mask of "modernity", those groups of young people, hide their real identity, which as authoress herself says can`t avoid being a traditional one.